Changes in the TCR repertoire of T‐cell subsets during culture of cytokine‐induced killer cells. Issue 20 (2nd October 2022) - Liang, Guozheng; Feng, Gang; Chen, Hui; Li, Ling; Hu, Jicong; Zhou, Chuandong; Li, Jiawen; Shen, Han; Wu, Fenglin; Tao, Changli; Liu, Yan; Zhang, Wenfeng; et al.
Abstract : Cytokine‐induced killer (CIK) cells are a group of highly heterogeneous T cells expressing diverse T‐cell antigen receptors (TCRs), but possessing wide major histocompatibility complex (MHC)‐unrestricted antitumour activity, which have been used in the treatment of many tumours. However, the clonal diversity of different T‐cell subsets and whether there is a certain clonal preference during CIK culture remains to be clarified. We found that the proportion of oligoclones seen in some subfamilies of freshly isolated T cells decreased in varying degrees after culturing. This indicates that the diversity of T‐cell clones had been restored to a certain extent. The diversity differed among different T‐cell subsets, as some TCR subfamily oligoclones mainly appeared in CD3 + CD56 + cells, which also indicates the heterogeneity of the CIK cell composition. Abstract : Oligoclones found in freshly isolated T cells decreased after culturing cytokine‐induced killer (CIK) cells, indicating that the diversity of T cells increased during the culture process. Furthermore, the diversity differed among different CIK cell subsets, as some T‐cell antigen receptor (TCR) subfamily oligoclones mainly appeared in CD3 + CD56 + cells. These results are helpful to further understand the role of CIK cells in immunotherapy.